Controllability of Partially Automated Driving functions – Does it matter whether drivers are allowed to take their hands off the steering wheel?. (November 2015) - Naujoks, Frederik; Purucker, Christian; Neukum, Alexandra; Wolter, Stefan; Steiger, Reid
Highlights: Controllability assessment of a system limited during Partially Automated Driving. Implementation of comprehensive take-over concept. Variation of permitted hands-off interval (Hands-on: 10 s vs. Hands-off: 120 s). Most drivers kept their hands on the steering wheel, even with Hands-off system. No impairment of ability to react to system limit due to longer hands-off interval. Abstract: Different motor vehicle manufacturers have recently introduced assistance systems that are capable of both longitudinal and lateral vehicle control, while the driver still has to be able to take over the vehicle control at all times (so-called Partial Automation ). While these systems usually allow hands-free driving only for short time periods (e.g., 10 s), there has been little research whether allowing longer time periods of hands-off driving actually has a negative impact on driving safety in situations that the automation cannot handle alone. Altogether, two partially automated assistance systems, differing in the permitted hands-off intervals (Hands-off system vs. Hands-on system, n = 20 participants per assistance condition, age 25–70 years) were implemented in the driving simulation with a realistic take-over concept. The Hands-off system is defined by having a permitted hands-off interval of 120 s, while the Hands-on system is defined by a permitted hands-off interval of 10 s. Drivers' reactions at a functional system limit were tested under conditions of high ecological validity: while driving in a traffic jam, participants unexpectedly encountered a time-critical situation, consisting of a vehicle at standstill that appeared suddenly and required immediate action. A visual-auditory take-over request was issued to the drivers. Regardless of the hands-off interval, all participants brought the vehicle to a safe stop. In spite of a stronger brake reaction with the Hands-on system, no significant differences between assistance levels were found in brake reaction times and the criticality of the situation. The reason for this may be that most of the drivers kept contact with the steering wheel, even in the Hands-off condition. Neither age nor prior experience with ACC was found to impact the results. The study thus demonstrates that permitting longer periods of hands-off driving does not necessarily lead to performance deficits of the driver in the case of take-over situations, if a comprehensive take-over concept is implemented.